2021
DOI: 10.3102/0013189x211056868
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Losing Postsecondary Student Grant Aid: Results From a Systematic Review

Abstract: With the goal of informing federal and state policy makers in a time of budget constraints, we used a systematic review methodology to identify and summarize findings from studies that examined the effects of losing grant aid due to policy changes and students’ failure to meet renewal requirements. Studies reviewed in this policy brief show negative effects on student outcomes when grant aid is reduced or eliminated. While results vary, this general conclusion applies when grant aid is reduced or eliminated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“… 11 This is similar to prospect theory which predicts that the negative effects of losing aid may be larger in magnitude than the positive effects of gaining aid, as “people are much more sensitive to losses–even small losses–than to gains of the same magnitude” LaSota et al (2022), citing Barberis (2013, p. 175) …”
mentioning
confidence: 71%
See 2 more Smart Citations
“… 11 This is similar to prospect theory which predicts that the negative effects of losing aid may be larger in magnitude than the positive effects of gaining aid, as “people are much more sensitive to losses–even small losses–than to gains of the same magnitude” LaSota et al (2022), citing Barberis (2013, p. 175) …”
mentioning
confidence: 71%
“…We aimed to estimate the effect of a policy that targeted low-income students (about two-thirds are Pell recipients) making satisfactory academic progress and removed financial support to finance college participation. Following loss aversion (Kahneman et al, 1990) (and/or prospect theory, see Barberis, 2013; LaSota et al, 2022) and the economic theory of the consumer (Barten & Böhm, 1982; Varian, 2010), we anticipated that becoming HOPEless was expected to negatively impact their academic outcomes. To assess the magnitude of this HOPEless effect, we comprehensively compared their credits attempted, credits attained, and persistence indicators against the outcomes of their not affected counterparts—including their targeted peers who never received HOPE, while relying on multiple analytic samples and analytic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of undocumented college students becoming suddenly eligible for aid is important to the broader financial aid literature because there are few examples of policies that drastically change aid eligibility for continuing students. While there is literature on the detrimental effects of losing aid (LaSota et al, 2022), in our search, we found just one study that examined how access to new aid affected the academic choices and retention of continuing students. Castleman et al (2018) found that eligibility for need-based financial aid increased STEM course enrollment and completion by 20% to 35% among academically ready Florida college students who were already enrolled (Castleman et al, 2018).…”
Section: Financial Aid Policiesmentioning
confidence: 99%
“…Prominent examples of this narrower focus include syntheses of impact evaluations of performance-based scholarships (Mayer et al, 2015), learning communities (Weiss, Visher, et al, 2015), grant aid (Nguyen et al, 2019), loss of financial aid (LaSota et al, 2021), and enhanced advising (Karp et al, 2021), plus the IES WWC practice guide on strategies for helping postsecondary students in developmental education (T. Bailey et al, 2016). These syntheses contribute substantially to the postsecondary "what works" knowledge base, but there are limitations.…”
Section: Introductionmentioning
confidence: 99%